Scenarios for a future electricity supply optimised variations on supplying Europe and its neighbours with electricity from renewable energies - Czisch, Gregor (The Institution of Engineering and Technology, 2011)
This book reviews developments in the following fields: solar energy; wind power; biomass utilisation; hydropower; geothermal energy utilisation; downdraught energy towers; hydrogen energy; fusion power plants; fossil-fired power plants; electricity consumption; power plant scheduling and planning; and electricity supply scenarios.